Hemodialysis and brain diseases in older individuals. Issue 4 (9th May 2022) - Iimura, Ayako; Sakakibara, Ryuji; Sawai, Setsu; Ogata, Tsuyoshi; Terayama, Keiichiro; Mizuno, Hirohito; Katsuragawa, Shuichi; Nagao, Takaaki; Nemoto, Masaaki; Suzuki, Keiko; Izawa, Kaori; Haruki, Shin‐ichi; et al.
Abstract: Background: It is known that age‐related brain symptoms (namely gait difficulty and/or dementia/delirium) occur in older individuals under hemodialysis (HD). However, it is not known which types of brain disease underlie such symptoms most. Objective: The aim of this study was to correlate brain symptoms with brain diseases in patients undergoing HD. Methods: This was a retrospective study at a multi‐faculty university hospital in Japan over a 12‐month period. All subjects were hospital inpatients undergoing HD (either started during hospitalization or maintenance therapy), with a diagnosis of brain symptoms resulting in referral to the neurogeriatric team (dementia/delirium support team, DST). Results: (1) More than half our HD patients (n = 133) were ≥ 65 years (mean age, 67 years) and male. (2) 37.6% of them showed brain symptoms and were DST‐referred, among whom 62.4% were > 65 years) ( P  < 0.05). (3) Of the referred patients, 16% had episodes of fall‐related surgery and 30% had aspiration pneumonia (all older). (4) 23.3% of referred patients needed restraint for the safety of HD (mostly older). (5) Most of the neurological disorders were age‐related brain diseases, for example, most commonly a combination of white matter disease (WMD) and Alzheimer's disease (AD) (85%, overlap counted), followed by alcoholism and dementia with Lewy bodies (DLB). Conclusion: In HD patients, age‐related brain symptoms (needed restraint for HD, or with recent fall and/or aspiration) increased with age. The most common underlying brain disease seemed to be a combination of WMD and AD.